Optimizing treatment duration with ramucirumab and paclitaxel by managing chemotherapy-associated toxicity: Review of four cases. (October 2020) - Merl, Man Yee; Moye, Renee; Chatterjee, Anindya; Ogburn, Kenyon D
Gastric and gastroesophageal junction adenocarcinomas have poor prognoses. Ramucirumab is considered a second-line standard of care for patients with these cancers. Patients may develop chemotherapy-induced adverse events, and physicians may benefit from greater familiarity with treatment management in the setting of common adverse events. We report four cases of metastatic gastric or gastric and gastroesophageal junction adenocarcinoma treated with second-line ramucirumab plus paclitaxel. All patients developed chemotherapy-associated grade ⩾2 neutropenia and/or neuropathy, and one experienced recurrence of neurotoxicity, during second-line therapy. These adverse events were successfully managed by withholding or reducing the paclitaxel dose, without modifying the ramucirumab dosage schedule, and allowed administration of additional therapy cycles. In all patients, second-line therapy was associated with a best overall response of complete or partial response ranging from 2.2 to 12.4 months. These four cases demonstrate that paclitaxel-associated adverse events can be managed with dose modifications, thereby allowing continued therapy and potential survival benefits.